Komunikasi Interpersonal Wanita Perokok Dalam Pertemanan Bukan Perokok: Studi Kasus di Tanjung Sari - Nur Adila Rahmah Farhana; Abdul Rasyid; Zuriah Zuriah (Lembaga Pengembangan Kinerja Dosen, 2024)
Interpersonal communication is face-to-face communication with the aim of getting feedback directly from the person, so that interpersonal communication can affect the relationship between one and the other. The study was to understand the impact of interpersonal communication between women who smoke in non-smoking friendship around Tanjung Sari, in the development of friendship between them by using the social penetrating theories of Altman and Taylor. It is a qualitative type of descriptive research with a case-study approach. The study collects data with in-depth interviews and observations. Research shows that there has been a development in the relationship between women who smoke in non-smokers even to a stable level where they can understand each other.